Once More about Acoustics of Impacts as a Factor of Ensuring Mutational and Evolutionary Transformations of the Environment - Pinchuk, Vladimir A.; Pinchuk, Anton V. (Innovations in Science and Technology Vol. 8, 2022)
Consider previously unexplored possibilities within the conceptual framework, Characteristics of the internal energy balance of material media were originally recognised by the authors (between their different physical nature energy states), the real involvement of acoustic disturbances experienced by media in the conditions of existence into making sure of their and the physical world as whole and mutational and evolutionary transitions is taken into account.